Leadership Narratives in Postsecondary Dance Administration: Voices, Values and Gender Variations. Issue 2 (3rd April 2017) - Risner, Doug; Musil, Pamela S.
ABSTRACT: Dance in the U.S. university finds its beginnings in the visionary leadership of women. Since the mid-1910s, dance faculty and students in higher education have been predominantly female. Gender in postsecondary dance today remains much the same, with the exception of dance leadership, which is increasingly male. This narrative inquiry is drawn from a mixed-method study ( n = 75) that examined the lives of administrative leaders—defined as chairs, directors, heads, or coordinators—who lead departments or programs of dance in colleges and universities in the U.S. The purpose of the exploratory investigation was to develop a status report drawn from quantitative survey data and qualitative interview narratives of administrators in postsecondary dance with particular attention to gender. This inquiry focuses on representative data of nine participants from the larger study. Findings are presented on participants' leadership approach; support for work; work–life balance; and research, creative activity and teaching. Gender implications are discussed.